THE RESULTS OF THE REHABILITATION PROGRAM APPLIED AFTER FLEXOR AND EXTENSOR TENDON INJURIES OF THE HAND - Ümit Seçkin; Pınar Borman; Mihriban Akyüz; Hatice Bodur; Bülent Erdoğan (Archives of Rheumatology, 2000)
We aimed to present our results of the rehabilitation program applied in patients with flexor and extensor tendon injuries of the hand. Twenty-five patients (25 hands, 40 tendons) with a mean age of 27.6 ± 13.4 years were included in the study. The intensity of spontaneous pain and pain with motion, range of motion in joints, alterations in total active motion (TAM), grip strength, pinch and lateral pinch strength were assessed before and after the rehabilitation program. At the end of the therapy, our results according to TAM system were excellent and good in 40 % of the flexor tendon injury group and 70 % of extensor tendon injury group. The mean TAM value was 190º and 230º in flexor and extensor tendon injury groups respectively. Grip strength was found to be good in 73 % of patients in extensor tendon group and 64 % in flexor tendon group. The values for the pinch strength were found to be good in 100 % and 83 % whereas lateral pinch strength were found to be 82 % and 90 % in groups of extensor and flexor tendon injuries respectively. All the parameters were significantly improved at the end of therapy on the 3rd month. In conclusion, the results of our rehabilitation program in extensor and flexor tendon injuries of the hands were found to be good and effective.